DIFFERENCES IN ATTITUDES OF FOURTH GRADE AND SEVENTH GRADE FEMALE STUDENTS TOWARD PHYSICAL EDUCATION CLASSES - Vučeraković, Milica (Sport - nauka i praksa, 2022)
The main aim of this research was to determine the differences in the attitudes of female students of fourth and seventh grade of elementary school toward Physical Education classes. The research has the transversal character and it was conducted at the elementary school "Oktoih" in Podgorica. The sample consisted of 50 students from the mentioned elementary school. Students were divided into two subdivisions, according to the age criteria and the grade they attended. The first sub-sample was composed of 25 female fourth grade students and the second was composed of 25 female seventh grade students. Anonymous standardized questionnaire survey, adapted to the needs of this research, was used. Questionnaire surveys were given to the girls who were explained how to fill them in. The questionnaires were observed and the received results were processed in a descriptive way and shown in a tabular way. Chi-squared test (p< 0.05) was used to determine statistically meaningful differences between fourth grade and seventh grade female students’ answers. The results have shown the existence of statistically significant differences considering favorite places of conducting Physical Education classes and pleasure in terms of the quality of Physical Education classes.